CULTURAL TRANSLATION OF SCIENTIFIC IMAGINATION: WHY JULES VERNE HAS NO DIRECT EQUIVALENT IN UZBEK LITERATURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Scientific imagination in literature is shaped not only by technological and epistemic developments but also by culturally specific narrative traditions. While nineteenth-century European literature produced a highly influential model of scienceoriented adventure fiction through the works of Jules Verne, Uzbek literature developed along a different trajectory shaped by historical, socio-political, and epistemological conditions. This article examines why Uzbek literature lacks a direct equivalent of Jules Verne by analyzing the cultural translation of scientific imagination across literary systems. Using comparative literary analysis and cultural narratology,
Keywords: scientific imagination, cultural translation, Uzbek literature, Jules Verne, comparative literature, science fiction, narrative modernity